Letter from Max Bredig to Georg Bredig, January 8, 1939 - Bredig, Max Albert (1939)
Max Albert Bredig (1902-1977) tells his father, Georg Bredig (1868-1944) that he will send him a guarantee of financial support while he is in Holland. Georg fled to Holland to stay with Ernst Cohen (1869-1944) when it became too dangerous for him to stay in Germany. Max continues to tell his father about his new job at the Vanadium Corporation of America.
Keywords: Cohen, Ernst, 1869-1944; Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Emigration and immigration; Jewish Holocaust (1939-1945); World War (1939-1945); Vanadium Corporation of America